The spatial structure of Baltic Sea ferry services - Andrei D. Katorgin (Immanuel Kant Baltic Federal University, 2021)
Ferry service is a transport system of regular routes which links areas separated by water bodies. Sometimes ferries are the only connection of an island and the mainland which is not rare in the Baltic Sea. A typical example of this is the island of Saaremaa. Ferry service is the backbone of cargo and passenger traffic in the Baltic Sea region.